2021
DOI: 10.1002/pca.3099
|View full text |Cite
|
Sign up to set email alerts
|

Application of multivariate linear regression models for selection of deep eutectic solvent for extraction of apigenin and luteolin from Chrysanthemum indicum L.

Abstract: Introduction Among a variety of compounds presented in chrysanthemum, apigenin and luteolin are the two main components that play a major role in numerous biological activities of this herb. Objectives We aimed to obtain linear models showing the dependence of the yield of extraction of apigenin and luteolin on the composition of deep eutectic solvent and investigate the extraction of these two ingredients from Chrysanthemum indicum L. Methods Two models showing the dependence of luteolin and apigenin concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In this study, the optimal time of extraction was determined to be 60 min, which was considerably shorter compared to other studies on the extraction of flavonoid from C. indicum using ethanol or water as solvents [23–25] . On the other hand, compared with our previous study using deep eutectic solvent, although we only carried out at room temperature, the use of HP‐β‐CD still increased the amount of extracted apigenin and luteolin by 2.50 times and 1.93 times, respectively [26] . These results suggested that HP‐β‐CD might be an attractive choice in the extraction of active ingredients from medicinal herbs in general.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…In this study, the optimal time of extraction was determined to be 60 min, which was considerably shorter compared to other studies on the extraction of flavonoid from C. indicum using ethanol or water as solvents [23–25] . On the other hand, compared with our previous study using deep eutectic solvent, although we only carried out at room temperature, the use of HP‐β‐CD still increased the amount of extracted apigenin and luteolin by 2.50 times and 1.93 times, respectively [26] . These results suggested that HP‐β‐CD might be an attractive choice in the extraction of active ingredients from medicinal herbs in general.…”
Section: Resultsmentioning
confidence: 57%
“…[23][24][25] On the other hand, compared with our previous study using deep eutectic solvent, although we only carried out at room temperature, the use of HP-β-CD still increased the amount of extracted apigenin and luteolin by 2.50 times and 1.93 times, respectively. [26] These results suggested that HP-β-CD might be an attractive choice in the extraction of active ingredients from medicinal herbs in general.…”
Section: Model Validationmentioning
confidence: 93%
See 1 more Smart Citation
“…This is due to the fact that at present there are both a large number of eutectic solvents themselves and a huge number of bioactive components of plants. This has led researchers to often use either a limited number of eutectic solvents to extract the maximum number of bioactive compounds 51–54 or, vice versa, large amounts of eutectic solvents to extract one particular type of substance 55–58 . Moreover, there is lack of reports on the use of original DESs without dilution.…”
Section: Introductionmentioning
confidence: 99%
“…This has led researchers to often use either a limited number of eutectic solvents to extract the maximum number of bioactive compounds [51][52][53][54] or, vice versa, large amounts of eutectic solvents to extract one particular type of substance. [55][56][57][58] Moreover, there is lack of reports on the use of original DESs without dilution. Majority of DESs are diluted before the extraction [59][60][61][62] to decrease viscosity, but this distorts the properties of the original solvents.…”
mentioning
confidence: 99%